2009
DOI: 10.1097/01.pra.0000364284.78457.ea
|View full text |Cite
|
Sign up to set email alerts
|

No Cathartic Effect in Suicide Attempters Admitted to the Emergency Department

Abstract: The goal of the present study was to test the hypothesis that suicide attempts have a cathartic effect. We retrospectively investigated sociodemographic and clinical characteristics of suicide attempters admitted to the emergency department of a university hospital who were referred for a psychiatric assessment. The participants were 158 consecutive patients admitted to the emergency department because of a suicide attempt between January, 2006, and February, 2007; controls were 360 consecutive psychiatric ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Such a high incidence of suicidal ideation just hours after the attempt is consistent with literature contesting the cathartic effect, i.e. the decrease in suicidal symptoms caused by the outward expression of suicidality via a suicide attempt [ 34 , 35 ]. Research by Beautrais found higher rates of further attempts and higher rates of subsequent suicide among patients who had made medically serious attempts and failed to be relieved to have survived, still wanting to die, and stating the intention to make a further attempt [ 36 ].…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Such a high incidence of suicidal ideation just hours after the attempt is consistent with literature contesting the cathartic effect, i.e. the decrease in suicidal symptoms caused by the outward expression of suicidality via a suicide attempt [ 34 , 35 ]. Research by Beautrais found higher rates of further attempts and higher rates of subsequent suicide among patients who had made medically serious attempts and failed to be relieved to have survived, still wanting to die, and stating the intention to make a further attempt [ 36 ].…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Patients whose suicide attempt was recent presented significantly higher levels of depressive symptoms, an observation consistent with many other reports indicating that most patients remain depressed following a suicide attempt. The patient’s mood usually improves after a therapeutic intervention [ 38 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent Centers for Disease Control Surveillance for Violent Deaths, 13.4% of people who had committed suicide had a diagnosis of bipolar disorder [2]. Among patients admitted to an emergency room for suicide attempts, those attempting suicide were five times more likely to have bipolar disorder than those presenting to the emergency room for non-suicide related psychiatric issues [12]. …”
Section: Introductionmentioning
confidence: 99%